Factors Affecting Customer Loyalty to Retailers: The Case of Vinmart+ Chain Store in Hanoi - Nguyen, Thi Quynh Minh (Khoa Quốc tế, ĐHQGHN, 2020)
The study aims to assess factors affecting customer loyalty to convenience store. The study was conducted with the participation of Hanoi consumers to the Vinmart+ chain store that is a domestic convenience chain store newly involved in the retail market of Vietnam from 2014 but has created a positive image and has been clearly positioned in the customers’ mind.